Дослідження методів збільшення широкосмуговості мікросмужкових антен. Частина 2: Багаторезонансний метод - Жовнович, А. В.; Гілімханов, Р. Р.; Гармаш, О. Ф. (ХНУРЕ, 2023)
The purpose of the work is to study methods for improving the design of microstrip antennas to expand its operating frequency band
Keywords: мікросмужкова антена